The Moderating Effect of Gender Equality and Other Factors on PISA and Education Policy - Janine Anne Campbell (MDPI AG, 2021)
Globalisation and policy transfer in education make it incumbent upon decision makers to prioritise among competing policy options, select policy initiatives that are appropriate for their national contexts, and understand how system-specific factors moderate the relationship between those policies and student outcomes. This study used qualitative comparative analysis and correlational analyses to explore these relationships with publicly available data on socio-economic, cultural, and education conditions, and their association with PISA 2015 results in 49 countries. Findings show that gender and income equality, human development, and individualism were outcome-enabling conditions for PISA 2015 results, and gender equality was the most consistent of these conditions. These factors significantly moderated the relationships between education policy and PISA results. Implications for the identification of meaningful peer countries for comparative educational research, policy transfer, and the future expansion of PISA are discussed.